Cardiac abnormalities induced by benzene exposure from the flaring disaster at the BP refinery plant in Texas City - Mark A. D'Andrea; Nadish Garg; Shubham Trehan; G. Kesava Reddy (International Journal of Occupational Medicine and Environmental Health)
Objectives Benzene exposure is associated with multiple adverse health effects on the human’s biological systems including its cardiac, pulmonary, respiratory, renal, liver, and other organs’ function. The purpose of this study is to assess the adverse health effects of benzene exposure on the cardiac functions in subjects affected by a flaring incident at the British Petroleum (BP) refinery in Texas City, Texas, USA.